BEHAVIOUR OF HOLLOW COLUMNS CONFINED WITH FRP - Kusumawardaningsih, Yuliarti; Tousi, Neda Fayaz; Nandang, Budi Sinaga (Semarang State University, 2009)
Confining columns with fiber reinforced polymer (FRP) composites have been investigated in the last few decades to answer problems in upgrading and retrofitting reinforced concrete (RC) columns; however, most studies concentrate on solid columns. This paper investigates the comparative behaviour of FRP confined hollow RC columns subjected to axial concentric loading. A total of twelve RC columns made from high strength concrete (HSC) were tested. Six of the columns had a circular cross section and five of them were hollow columns.Â The remainder columns had a square cross section, similarly five of them were hollow columns. Six columns from each configuration were left unconfined as control specimens, while the others were confined with FRP. It was found that FRP confinement increased hollow RC columnsâ€™ axial load and ductility capacities; and hollow columns having circular holes had better performance compared to hollow columns having square holes. Pelapisan kolom dengan komposit fiber reinforced polymer (FRP) telah diteliti selama beberapa tahun terakhir untuk menjawab masalah-masalah dalam peningkatan dan retrofit kolom-kolom beton bertulang; tetapi kebanyakan penelitian berkonsentrasi pada kolom-kolom solid. Tulisan ini mengungkapkan perbandingan perilaku dari FRP yang melapisi kolom beton bertulang berlubang yang dibebani oleh beban aksial terpusat. Sejumlah dua belas kolom terbuat dari beton mutu tinggi di uji. Enam kolom memiliki penampang bundar, dimana lima diantaranya adalah kolom berlubang. Kolom lainnya memiliki penampang persegi, dimana lima diantaranya adalah juga kolom berlubang. Enam kolom dari tiap konfigurasi tidak dilapisi oleh FRP berperan sebagai kolom control, sedangkan yang lainnya dilapisi dengan FRP. Dihasilkan bahwa pelapisan dengan FRP meningkatkan beban aksial dan kapasitas daktilitasÂ kolom berlubang; kolom dengan lubang bundar memiliki perilaku yang lebih baik daripada kolom dengan lubang persegi.